USING ARTIFICIAL NEURAL NETWORKS FOR PREDICTING MATERNAL DEATHS AT CHITUNGWIZA CENTRAL HOSPITAL IN ZIMBABWE - DR. SMARTSON. P. NYONI,; MR. THABANI NYONI, (International Journal of Innovations in Engineering Research and Technology, 2021)
In this research paper, the Artificial Neural Network model has been used to model maternal deaths at Chitungwiza Central Hospital (CCH) in Zimbabwe. The study covers the period January 2012 to December 2019. The out-of-sample forecasts range over the period January 2020 to December 2021. The residual analysis of the model also further indicates that the model applied in this paper is stable and suitable for forecasting maternal deaths at CCH. The forecasts show a generally upwards trajectory of maternal death cases at CCH over the period January 2020 – December 2021. The paper offers a six-fold policy recommendation for use by the CCH health executive.